2021
DOI: 10.3389/fimmu.2021.790469
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Antibody Responses to SARS-CoV-2 in Patients With Mild or Moderate COVID-19 Who Received Bamlanivimab Alone or Bamlanivimab and Etesevimab Together

Abstract: BackgroundNeutralizing monoclonal antibodies (mAbs) to SARS-CoV-2 are clinically efficacious when administered early, decreasing hospitalization and mortality in patients with mild or moderate COVID-19. We investigated the effects of receiving mAbs (bamlanivimab alone and bamlanivimab and etesevimab together) after SARS-CoV-2 infection on the endogenous immune response.MethodsLongitudinal serum samples were collected from patients with mild or moderate COVID-19 in the BLAZE-1 trial who received placebo (n=153)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Our study agrees with the recent report of Zhang et al [ 33 ]. That study examined the endogenous anti-SARS-CoV-2 antibody response in BAM and BAM + ETE treated subjects by measuring antibody titers against portions of the spike protein not recognized by the mAb.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study agrees with the recent report of Zhang et al [ 33 ]. That study examined the endogenous anti-SARS-CoV-2 antibody response in BAM and BAM + ETE treated subjects by measuring antibody titers against portions of the spike protein not recognized by the mAb.…”
Section: Discussionsupporting
confidence: 94%
“…A recent mouse study showed that passive antibody suppressed not only the IgM response but also the IgG and memory B cell response [ 22 ]. The reduced antibody titers reported at 85 days after mAb treatment by Zhang et al [ 33 ] suggests this might be the case. Still, this has yet to be demonstrated in humans and would apply only to the humoral response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there was the potential for bamlanivimab to markedly reduce the endogenous immune response to COVID-19 vaccination. However, similar to previous findings ( 53 ), any reduction in antigen load due to therapeutic mAbs was not sufficient to severely blunt the immune response, in this case to COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…As such, most participants far exceeded the in vitro estimated IC90 (4.1 μg/mL) at the time of vaccination ( 30 ). Therapeutic mAbs for COVID-19 are known to reduce viral load ( 7 , 52 ) and we have previously shown that high viral load is associated with high antibody titers ( 53 ). Therefore, there was the potential for bamlanivimab to markedly reduce the endogenous immune response to COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven mAb neutralizing drugs including bamlanivimab, etesevimab, casirivimab, imdevimab, sotrovimab, cilgavimab, and tixagevimab either as monotherapy or as combination therapy have been approved or received EUAs from the U.S. FDA for the treatment of COVID-19 (Agarwal et al, 2020;Shi et al, 2020a;Zhang et al, 2021c;Nathan et al, 2021). All repurposed drugs with their mechanism of actions against SARS-CoV-2 infections are shown in Table 1.…”
Section: Repurposing Drugs For Covid-19: Concept and Mechanism Of Actionmentioning
confidence: 99%